THE NEXT CLICK: FACTORS DRIVING OTT PLATFORM ADOPTION - Vaghela, Nilrajsinh; Pandya, Kerav (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In India, OTT services have grown exponentially, changing the entertainment and media scene. OTT adoption in India is examined in this article, including its drivers, trends, and consequences. This research synthesises academic literature, industry reports, and empirical investigations to identify OTT adoption drivers in India. These include inexpensive cellphones, increased internet connectivity, rising disposable incomes, and customer desires for on-demand entertainment. Researcher have use variables of UTAUT model which is technology adoption model to identify the intention to adopt OTT platform.